Meteorological soundings during the FINNARP-95/96 expedition in the Weddell Sea ... - Launiainen, Jouko; Vihma, Timo; Uotila, Petteri; Kosloff, Pekka; Purokoski, Tero; Kalliosaari, Simo; Välisuo, Ilona (Finnish Meteorological Institute, PL 503, 00101 Helsinki, 2018)
Studies of atmospheric boundary layer and air-sea-ice interaction were carried out in the Weddell Sea during FINNARP-95/96 expedition. Here we present the meteorological soundings that were performed during the campaign onboard R/V Aranda. The soundings were done in January and February 1996. The soundings were carried out with Vaisala RS80-15N and RS80-15G radiosondes, which measure the air pressure, temperature and relative humidity . A detailed description of the atmospheric soundings can be found in the technical report Vihma, et al.: “FINNARP Air-Sea-Ice Interaction Experiment in the Weddell Sea in 1996-1997”, Antarctic Reports of Finland, Report No 7, 1997, published by the Ministry of Trade and Industry, Helsinki, Finland. ...